2014
DOI: 10.1007/s10195-013-0278-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary total hip arthroplasty versus internal fixation in displaced fracture of femoral neck in sexa- and septuagenarians

Abstract: BackgroundThe optimal treatment of femoral neck fracture in the elderly patient is still under debate. In patients aged 60–80 years, the decision between internal fixation and arthroplasty remains controversial. The primary aim of the present study is to evaluate the functional outcome of patients aged 60–80 years with femoral neck fracture treated with total hip arthroplasty or closed reduction and internal fixation. The secondary aim is to evaluate the incidence of nonunion and avascular necrosis in femoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Mild thigh pain was present in 4 patients. When compared to the approaches used by other investigators, our group had a lower dislocation rate and mortality rate (Table 2) [23][24][25][26][27][28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 64%
“…Mild thigh pain was present in 4 patients. When compared to the approaches used by other investigators, our group had a lower dislocation rate and mortality rate (Table 2) [23][24][25][26][27][28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 64%
“…[2223242526272829] The primary reasons for exclusion were as follows: six were review articles,[113031323334] six reported data that did not pertain to intracapsular hip fractures,[31535363738] one was a correspondence letter,[39] and two studies were excluded because they were not RCTs. [4041] Details of the selection process are shown in Figure 1. The weighted kappa for the agreement on eligibility between the reviewers was 0.88 (95% CI [0.83–0.94]).…”
Section: Resultsmentioning
confidence: 99%
“…In this group of 146 hips in patients who were at least 75 years old, there was also no difference in mortality between the groups. Other studies have also found a higher risk of revision surgery after internal fixation and recommend arthroplasty for healthy, lucid elderly patients 30 33 . Although the rate of re-operation is lower, it should be recognized that arthroplasty introduces a distinct subset of complications, namely dislocation, aseptic loosening, infection, and wound complications.…”
Section: Arthroplasty For Hip Fracturesmentioning
confidence: 95%